An empirical modeling approach for the ignition delay of fuel blends based on the molar fractions of fuel components. (15th January 2016) - Ma, Jianan; Kwak, Kyoung Hyun; Lee, Byungchan; Jung, Dohoy
Abstract: An empirical ignition delay model has been developed for the fuel blends of isooctane, n -heptane, toluene and ethanol based on their molar fractions in the stoichiometric condition. The model employs traditional Arrhenius type correlation and cool-flame temperature rise correlations to describe the negative temperature coefficient (NTC) region for the fuel blends. The overall ignition delay of a fuel blend is correlated with individual ignition delay information based on the molar fraction of the fuel component in the mixture. The proposed model is successfully validated against the published experimental ignition delay data using various binary, ternary and quaternary fuel blends of isooctane, n -heptane, toluene and ethanol.